Osvaivay nedra kompleksno, po-khozyayski! - Tupitsyn, Yuri Sergeyevich (Плакат СССР (Plakat), 1976)
Hands holding bursting molecule amid scenes of industry Original title: Осваивай недра комплексно, по-хозяйски! PO-0136